Nightshift work job exposure matrices and urinary 6-sulfatoxymelatonin levels among healthy Chinese women - Bu-Tian Ji; Yu-Tang Gao; Xiao-Ou Shu; Gong Yang; Kai Yu; Shou-Zheng Xue; Hong-Lan Li; Linda M Liao; Aaron Blair; Nathaniel Rothman; Wei Zheng; Wong-Ho Chow (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVE: Six-sulfatoxymelatonin (aMT6s) is a primary urinary metabolite of melatonin. We examined the association between aMT6s levels and shift work estimated by a job exposure matrix (JEM) among healthy participants of the Shanghai Women's Health Study. METHODS: Creatinine-adjusted aMT6s levels were measured in the urine samples of 300 women and related to JEM shift work categories. RESULTS: Adjusted geometric means of aMT6s levels from urine samples collected before 08:00 hours were lower among persons holding nighttime shift work jobs. The adjusted aMT6s levels (ng/mg creatinine) were 8.36 [95% confidence intervals (95% CI) 4.47-15.6], 6.37 (95% CI 3.53-11.5), 6.20 (95% CI 3.33-11.5), 3.81 (95% CI 2.02-7.19), and 3.70 (95% CI 1.92-7.11) from the lowest (never held a shift work job) to the highest (current job likely involved all-night shift work) shift work JEM scores (P=0.05). CONCLUSION: Our results indicate that nightshift work JEM scores were significantly and inversely associated with aMT6s levels in early morning spot urine samples collected between 07:00-08:00 hours.